Exploration of Social Accounting Disclosures: A Bibliometric Analysis Perspective - Muthohirin; Kanthi Riska Rahayu; Fahayu Priristia (UNIB Press, 2024)
This study reviews the literature related to social accounting disclosures with the aim of mapping the research that has been done, providing insight into research trends, providing an overview of research themes, identifying the most cited authors and journals, evaluating the most active affiliations and countries in discussing social accounting reporting disclosures, and providing a basis for future research directions. Data analysis was conducted using bibliometric methods by collecting data from 188 articles contained in journals indexed in the Scopus database. RStudio was used as software to analyze the data and break down research trends by author, journal, affiliation, country, and keywords, providing insights into future research opportunities. The review showed an increase in publications since 2003, with Khaled Hussainey and Mathias Laine as the most active authors and Khaled Hussainey as the most impactful author. The most relevant journal in this context is Accounting, Auditing, and Accountability. The University of Naples Parthenope is the most relevant affiliation regarding publications in this field. In addition, the UK plays a leading role in this literature both in terms of the number of published works and the most cited ones. The most relevant keywords are corporate social responsibility, sustainability, and sustainable development. The implications of this study are significant for researchers interested in social accounting disclosures. The study provides a comprehensive overview of the research that has been done in this field, identifying research trends, themes, and the most cited authors and journals. This information can be used to guide future research directions and to identify areas where further research is needed